Cultivation of promising aquatic plant species for sustainable development of Central Asian biodiversity - Karimov Bolotbek; Boronbaeva Ainazik; Dursunbaeva Aida; Abdyrakhmanova Zhazgul; Karimov Meder; Israilova Gulbarchin; Kholmuradova Totigul (E3S Web of Conferences)
The article deals with the development of reliable methods of mass cultivation and ways of rational use of some aquatic plants such as:Wolffia arrhiza L.),Lemna minor L.),Azolla caroliniana Willd.) andPistia stratiotes in conditions of Kyrgyzstan and Uzbekistan; The results of experiments to determine the optimal mineral, organomineral and organic nutrient media are discussed, and the optimal concentration of wastewater from urban sewers, livestock complexes for better growth of the studied plants is determined. It is also noted that Wolffia arrhiza L., Lemna minor L., Azolla caroliniana Willd. and Pistia stratiotes can be grown in aquariums and fiberglass trays in greenhouses (in winter) and in concrete pools under the open sky (in summer), and that effective nutrient media for cultivation of the studied plants are manure (sheep, cow, horse manure), chicken manure, wastewater from municipal sewage treatment plants and industrial enterprises, as well as mineral media of Nakamura, Landolt, Lukina and Knop. The authors cite the results of hydrochemical and microbiological studies, which show that complete purification of wastewater from organomineral substances and pathogenic microorganisms occurs within 12-15 days.